TURIZM MAMLAKATDA IQTISODIY-IJTIMOIY ALOQALARNI RIVOJLANTIRISH OMILI - Sharipova, Sh.B. (SCIENCE and SOCIETY, 2022)
The article discusses the impact of tourism on international and socio-economic development of the country and the current problems of its assessment, the direct and indirect impact of tourism on the country's economy. Tourism contributes to GDP growth, foreign exchange earnings and investment, and the development of industry, trade and social infrastructure. In today's world, there is talk of the importance of tourism as а sector of the economy.
Keywords: tourism; national economy; socio-economic development; the impact of tourism; direct impact; indirect impact